POTENTIAL OF GREEN TEA INFUSION IN REDUCING LUNG MDA LEVELS OF BALB/C MICE DUE TO EXPOSURE TO ELECTRIC CIGARETTE VAPOR - Adnyana, I Made Diatmika; Wahyuniari, Ida Ayu Ika; Linawati, Ni Made; Arijana, I Gusti Kamasan Nyoman (E-Jurnal Medika Udayana; Vol 13 No 8 (2024): E-Jurnal Medika Udayana, 2024)
This research aims to evaluate the potential of green tea infusion in reducing Malondialdehyde (MDA) levels in the lungs of mice exposed to electronic cigarette vapor. The research employed an experimental method with a Randomized Post-Test Only Control Group design. The research sample consisted of 20 male mice aged 3-4 months with an average weight of 30 grams, divided into four groups: normal group (CN), negative control (NC), treatment 1 with a dosage of green tea 0.03 g (T1), and treatment 2 with a dosage of green tea 0.06 g (T2). After the treatment, an analysis of MDA levels in the mice's lungs was conducted by TBARS test. The average levels of MDA in mice were obtained as follows: CN=12.669 µM, NC=23.940 µM, T1=10.997 µM, T2=14.395 µM. Statistical analysis using the One-Way ANOVA test revealed significant differences (p<0.05) between CN and NC, NC and T1, and NC and T2. These findings indicate that green tea infusion has the potential to reduce MDA levels in the lungs of mice exposed to electric cigarette vapor. Thus, this research provides a foundation for further studies regarding optimal dosage and the mechanism of action of green tea infusion in combating the negative effects of exposure to electronic cigarette vapor on respiratory organs.